Factors influencing HPV vaccine hesitancy among university students in China: A cross-sectional survey utilizing the 3Cs model - Yuancheng He; Xiuqing Zhang; Jie Li; Yuehua Chen; Lin Zhang; Yuehong Wei (Human Vaccines & Immunotherapeutics)
The HPV vaccine, which has been demonstrated to be an effective method of reducing the risk of developing cervical cancer, is still being underutilized among college students in China. To assess the current status of HPV vaccine hesitancy among college students in Guangdong Province after the COVID-19 outbreak, and to systematically analyze the influencing factors of HPV vaccine hesitancy and construct a prediction model based on the WHO 3Cs model. A cross-sectional web-based survey was conducted in June 2023 among female college students in four cities in Guangdong Province. The data were analyzed using binary logistic regression with a focus on the 3Cs model: Complacency, Convenience, and Confidence. LASSO regression was employed to analyze the variables deemed to be of significance and to construct predictive models. Out of 1399 participants, 86.5% expressed no hesitancy toward HPV vaccination. However, 11.9% exhibited hesitancy, and 1.6% refused vaccination altogether. Factors such as trust in vaccine efficacy, perception of HPV infection risk, price considerations, and constraints like distance or time were significant contributors to hesitancy. Knowledge of the HPV vaccine, socio-demographic characteristics, and the educational level of participants’ mothers also played a role in vaccine hesitancy. It is recommended that targeted interventions be implemented within educational institutions with the aim of raising awareness of cervical cancer and HPV vaccines, simplifying the scheduling of vaccination appointments, and increasing affordability through the implementation of strategic purchasing measures or subsidy schemes.